(untitled) (Baghdad Science Journal, 2013)
In the present work, 9-fluorenone-2-carboxylic acid methyl ester (1) was prepared from 9-fluorenone-2-carboxylic acid and then converted into the acid hydrazide (2). Compound (2), is the key intermediate for the synthesis of several series of new compounds such as substituted 1,3,4-oxadiazole derivatives (3-6) were synthesized from the condensation of different substituted benzoic acids with compound (2) using POCl3 as condensing agent. Treatment of compound (2) with formic acid gave the N-formyl hydrazide (7), which upon refluxing with phosphorous pentoxide in benzene yielded the corresponding 5-(9-fluorenone-2-yl)-1,3,4-oxadiazole (8). Reaction of hydrazide (2) with phenyl isocyanate to give N-phenyl semicarbazide derivative (9), then this compound (9) convert to 5-(9-fluorenone-2-yl)-N-phenyl-1,3,4-oxadiazole-2-amine (10) via intramolecular cyclization by syrup H3PO4. Also the hydrazide (2) was treated with CS2/KOH afforded 5-(9-fluorenone-2-yl)-1,3,4-oxadiazole-2-thiol (11). Compound (11) was used to react with various alkyl halides and secondary amines to give 5-(9-fluorenone-2-yl)-1,3,4-oxadiazole-2-alkyl thiol (12-15) and 5-(9-fluorenone-2-yl)-1,3,4-oxadiazole-2-N-alkyl (16-19) derivatives respectively.